It takes a village: community education predicts paediatric lower-respiratory infection risk better than maternal education. Issue 2 (6th August 2009) - Gessner, Bradford D; Chimonas, Marc-Andre R; Grady, Sue C
Abstract : Background: Few studies have evaluated the contribution of community and parental education levels in determining paediatric outcomes, including lower-respiratory infection (LRI), the leading global cause of child mortality. Methods: The authors evaluated the association between community and maternal educational attainment and LRI risk among Medicaid-enrolled children age <2 years in Alaska, which has one of the highest LRI incidences ever reported. An individual-level database was created by linking Medicaid data to birth certificate files. A community-level database was created by calculating community LRI incidence rates and linking these values to Department of Labor census variables. Multilevel modelling was used to evaluate the independent effects of maternal and community education levels on LRI risk. Results: Statewide outpatient and inpatient LRI incidences were high at 42 and 6 per 100 child-years. When controlling for potential individual and community level confounding variables, a child's risk of outpatient and inpatient LRI was independently predicted in a dose–response manner by the child's mother's educational attainment and the educational attainment of other adults in the child's community. The latter variable had a stronger association and higher community education levels substantially mitigated the risk of poor maternal education. Conclusions: LRI risk among Alaskan children is affected by the formal education levels of the child's mother and other adults in their community. The mechanisms by which community education might influence LRI risk remain unknown and may include access to medical knowledge or acceptance of scientific versus traditional beliefs.